Using Readers Theater to Differentiate Instruction - Jamey Burson, (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2022)
Regardless of grade level, English Language Arts (ELA) teachers are faced with the challenge of providing effective reading instruction to students that represent a variety of skill and interest levels. While no “one-size-fits-all” approach exists, research shows that using drama-based literacies such as Readers Theater help differentiate instruction and contribute to increased levels of fluency, engagement, and comprehension for pre-K-12 learners. This article will provide the reader with an understanding of Readers Theater, explore the current research regarding its impact, and provide suggestions for implementation in an ELA classroom.